HUBUNGAN PENGETAHUAN DAN SIKAP IBU NIFAS TERHADAP PEMBERIAN KOLOSTRUM PADA BAYI BARU LAHIR DI KLINIK BERSALIN SRI KESUMA, STr. Keb - siti romlah (Institut Kesehatan dan Teknologi Al Insyirah, 2020)
Colostrum represent first dilution times of by bosom gland in form of pregnant brass chromatic dilution antibody and compared to higher protein milk of matur. Pursuant to survey early at home Pain Ms. and Child Expectation Mother from 10 child bed mother people, 6 people (60%) which not give colostrum and 4 people (40%) giving colostrum newborn baby. Target of this research is to know knowledge and child bed mother attitude to of colostrum newborn baby at clinic Sri Kesuma STr. Keb. This Research type quantitative with sectional cross desain. Research at clinic Sri Kesuma STr. Keb from Januari-Maret 2020. Population in this research amount to 60 child bed mother people. used Sampel counted 37 child bed mother people with technique of accidental sampling. Analysis the used analysis of univariat bivariate and. variable of Dependen of independent variable and kolostrum attitude and knowledge. Result of research prove that there is have a meaning knowledge to of colostrum (value p = 0,002), and there have a meaning attitude to of colostrums (value p = 0,006). Researcher suggest to health energy at clinic Sri Kesuma STr. Keb to give information about benefit or is important of colostrum newborn baby and expected also to be more improve Initiation Milk program Early (IMD) so that all child bed mother at clinic Sri Kesuma STr. Keb give colostrum to its baby.